The effect of a written and pictorial home exercise prescription on adherence for people with stroke - Kara, Sheetal Rowjee (My University, 2015)
Introduction: In South Africa the prevalence of patients with stroke that need help with at least one activity of daily living is equal to that of high income countries. Care of persons with stroke is essential, as stroke can lead to neurological deficits which in turn lead to functional impairments. Functional recovery for a patient, who has suffered a stroke, begins with rehabilitation. It has been found that supervised rehabilitation in an institution or at home improves the patient’s quality of life and fitness. It may not be feasible however, for the physiotherapist to supervise all rehabilitation, especially in a home-environment. Therefore adherence to exercise programmes is important. Adherence to exercise programmes allows for a potential saving in treatment costs, may avoid morbidity and unwanted side effects. The mode of exercise prescription may affect adherence to a home exercise programme. There are studies that show that the use of verbal prescription with an added brochure (a written and pictorial home-exercise programme) improves adherence rates. However none of these studies have been conducted in patients with stroke. Aim: The aim of this study was to determine the effect of a written and pictorial home exercise prescription on adherence with a home-exercise programme in patients with stroke at the Chris Hani Baragwanath Academic Hospital (CHBAH). Method: A randomised controlled trial with a blind assessor. Ethical clearance was applied for at the University of the Witwatersrand and permission to conduct the study was also obtained from CHBAH physiotherapy department and the superintendent before the commencement of the research project. Written informed consent was obtained from the patient and the caregiver before being included into the study. Participant’s anonymity was kept. All participants’ and their caregivers’ demographic data was captured on the initial assessment. The control group received a verbal home-exercise programme only and the experimental group received a verbal home-exercise programme with written and pictorial instructions for the exercises. An exercise logbook was completed by the participant’s caregivers to monitor adherence for each group. The Modified Rivermead Mobility Index (MRMI) and Barthel Index (BI) were used to establish mobility and activities of daily living functional ability of the patients. The significance of the study was set at 0.05. Between group comparison for the categorical data was carried out using the Chi square test. The Wilcoxon sign rank test was used for the between group comparison for the continuous data, the non-parametric data from the functional outcome measures as well as the adherence rates. Lastly the Spearman’s rank correlation co-efficient was conducted to assess if there is a relationship between the level of adherence and functional outcome in patients with stroke. Results: The average age of the participants was 60.8 (SD: 15.5) years. The gender distribution of the study population was 52% male and 48% female. Majority (76%) of the caregivers were females. Majority of the study population was living with a stroke for one to three months. The average length of stay in hospital was 14.5 (SD: 8.3) days. Of the study population 64% received in-patient physiotherapy. There was no significant difference between the intervention and control group for functional change and adherence: MRMI (p = 0.4), BI (p = 0.65) and adherence (p = 0.53). In the intervention group there was a greater increase in the MRMI score compared to the control group. But for the BI score the increase was greater in the control group. The relationship between functional ability (MRMI and BI) and the level of adherence for both the control and intervention group was generally not statistically significant. However, there was a weak relationship (p = 0.05, r = 0.44) for the intervention group for adherence and BI scores. Conclusion: The adherence rates were similar for the two groups despite the intervention that was administered. Both groups benefitted from the exercise therapy despite the mode of exercise prescription. Therefore there is no need to change the clinical practice at CHBAH regarding mode of home exercise prescription. Instead focus needs to be placed on interventions that can improve adherence to home exercise programmes e.g. the implementation of a monitoring system such as an exercise logbook.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2015
Keywords: Stroke; Stroke/rehabilitation